The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s40816-021-00333-w
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and pharmacological investigation of the ethanol extract of Byttneria pilosa Roxb.

Abstract: Background Traditionally, the herb Byttneria pilosa Roxb. is used for bone fractures, boils, scabies, rheumatalgia, snake bites, syphilis, elephantiasis, poisoning, and eye infection. Scientific reports suggest that it has significant anti-inflammatory, analgesic, anti-diarrheal, anxiolytic, locomotion, sedative and anti-obesity effects. This study aims at the investigation of the phytochemical and pharmacological properties of the ethanol extract of this herb. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Even though Fakoya et al [64] did not detect tannins and phenols in the EtOH extract of D. confragosa from Nigeria, this solvent is effective for the extraction of terpenoids, especially after the HD procedure. Hence, we assume that the DCHD extract also likely contains saponins, which are glycosides containing terpenoids or steroids [45,65]. This assumption was based on previous research, where the reactions typical of the detection of saponins themselves, observed in the species Meripilus giganteus, were foaming along with hemolysis of the cell membrane of erythrocytes [66].…”
Section: Hemolytic Activitymentioning
confidence: 97%
“…Even though Fakoya et al [64] did not detect tannins and phenols in the EtOH extract of D. confragosa from Nigeria, this solvent is effective for the extraction of terpenoids, especially after the HD procedure. Hence, we assume that the DCHD extract also likely contains saponins, which are glycosides containing terpenoids or steroids [45,65]. This assumption was based on previous research, where the reactions typical of the detection of saponins themselves, observed in the species Meripilus giganteus, were foaming along with hemolysis of the cell membrane of erythrocytes [66].…”
Section: Hemolytic Activitymentioning
confidence: 97%
“…In Tripura, elephantiasis is treated externally by applying the root of B. pilosa to afflicted areas ( Jyoti et al, 2020 ). Phytochemical analysis of the whole plant has revealed the presence of phenols, tannins, steroids, alkaloids, glycosides, flavonoids, saponins, and terpenoids ( Sikder et al, 2022 ). There has been limited exploration into the pharmacological potential of the leaf of B. pilosa .…”
Section: Introductionmentioning
confidence: 99%
“…This plant is characterized as a glabrous herb that completes its life cycle within a year, making it suitable for annual cultivation. It reproduces through seeds and reaches maturity during the winter season (Sikder et al, 2022).…”
Section: Introductionmentioning
confidence: 99%